Dari Alam ke Seni: Kreativitas Mempertahankan Warisan Lokal Melalui Budidaya Daun Lais dan Mengkuang Menjadi Tikar di Desa Jangkang Kecamatan Dendang Kabupaten Belitung Timur - Putra, Ramadan Dwi; Saparingga, Helen; Kartika, Nur Dwi; Saktifa, Romi (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2024)
This research explores the preservation of tradition through woven crafts in Nyuruk Village. Using an ethnographic approach, this study highlights how weaving skills are passed down from generation to generation, as well as their role in maintaining local cultural and economic identities. In addition, this research explores the social and economic dynamics behind the practice of weaving, including the role of women and the economic contribution of woven crafts to the local community. The results showed that woven crafts not only became a symbol of culture, but also served as an important source of income for villagers. Thus, efforts to preserve this tradition become important for the sustainability of local culture and economy.